Song Transmission as a Formal Cultural Practice - Stadler Elmer, Stefanie (Frontiers in Psychology, 2021)
From a biological point of view, the singing of songs is based on the human vocal learning capacity. It is universally widespread in all cultures. The transmission of songs is an elementary cultural practice, by which members of the older generations introduce both musico-linguistic rules and affect-regulative means to the younger ones. Traditionally, informal singing in familiar settings primarily subserves affect-regulation goals, whereas formal song transmission is embedded in various normative claims and interests such as preserving cultural heritage and representing collective and national identity. Songs are vocal acts and abstract models that are densely structured and conform to cultural rules. Songs mirror each generations’ wishes, desires, values, hopes, humour, and stories, and rest on unfathomable traditions of our cultural and human history. Framed in the emerging scientific field of didactics, I argue that research on formal song transmission needs to make explicit the norms and rules that govern the relationships between song, teacher and pupils. I investigate these three didactic components, first, by conceptualising song as rule-governed in terms of a grammar since songs for children’s are the most elementary musico-linguistic genre. This Children’s Song Grammar is based on the syllables as elements and on syntactics rules concerning the timing, tonality, and poetic language. It makes it possible to examine and evaluate songs in terms of correctness and well-formedness. Second, the pupils’ learning of a target song is exemplified by an acoustical micro-genetic study that shows how vocalization is gradually adapted to the song model. Third, I address the teachers’ role in song transmission with its normative accounts and give exemplary insights into how we study song teaching empirically. With each new song, a teacher teaches the musico-linguistic rules that constitute this genre, and conveys related cultural feelings. Formal teaching includes self-evaluation and judgements with respect to educational duties and aesthetic norms. This study of the three-fold didactic process shows song transmission as experiencing shared rule-following that induces feelings of well-formedness. I argue that making the inherent normativity of this process more explicit – here on a descriptive and conceptual level – increases the systematicity of this research domain.